THE ROLE OF VILLAGE-LEVEL ECONOMIC DIGITALIZATION IN OPTIMIZING MSMES IN NORTH ACEH; A CASE STUDY OF THE “KASIRAJA!” WEBSITE - Raisha Raza; Siti Hudaya (PT. Radja Intercontinental Publishing, 2026)
Micro, Small, and Medium Enterprises (MSMEs) are the backbone of Indonesia’s economy, with approximately 64.2 million business units contributing 61.07% to the national Gross Domestic Product (GDP) and absorbing 97% of the national workforce. However, despite their significant role, many MSMEs, particularly in North Aceh, still rely on manual record-keeping systems that are time-consuming, prone to errors, and hinder effective reporting. This condition reduces operational efficiency and weakens competitiveness in the digital era. This study offers a solution through the development of “KasirAja!”, a web-based cashier system designed to meet the needs of local MSMEs. By employing questionnaire methods and conducting system trials with business owners, this research analyzes the limitations of manual record-keeping and evaluates the effectiveness of a digital system in improving transaction speed, report accuracy, and user satisfaction. The expected outcome of this research is not merely the development of a cashier application, but the introduction of a transformative solution for MSMEs in North Aceh that enables faster, more organized, transparent, and modern business management. Through “KasirAja!”, MSMEs are expected to focus more effectively on strategic development, market expansion, and service improvement. Therefore, this study contributes not only a technological innovation but also a concrete effort to strengthen the village-level economy and prepare MSMEs in North Aceh to compete at the national and international levels.